Bank restructuring under asymmetric information: The role of bad loan sales - Segura, Anatoli; Suarez, Javier (Journal of Financial Intermediation, 2023)
We study restructuring solutions to the debt overhang problem faced by banks with a deteriorated loan portfolio in the presence of asymmetric information on loan quality. Classical liability restructuring solutions fail to work because banks can overstate the severity of their bad loan problem to obtain additional concessions from existing creditors. A sufficiently large loan sale requirement to the restructuring banks discourages such an opportunistic behavior, so a suitably chosen menu of loan sales cum liability restructuring is able to solve the debt overhang. We discuss the implementation of such a solution for banks funded with insured deposits through loan sales to outside investors supported by an asset protection scheme sponsored by the deposit insurance fund.